2022
DOI: 10.1101/2022.08.18.504437
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Toll pathway mediates Drosophila resilience to Aspergillus mycotoxins through specific Bomanins

Abstract: Host defense against infections encompasses resistance, which targets microorganisms for neutralization or elimination, and resilience/disease tolerance, which allows the host to withstand/tolerate pathogens and repair damages. In Drosophila, the Toll signaling pathway is thought to mediate resistance against fungal infections by regulating the secretion of antimicrobial peptides, potentially including Bomanins. We found that Aspergillus fumigatus kills Drosophila Toll pathway mutants without invasion because … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…In this last case, we imagine that functional Mtk might interact with the pathogen in some complex way to enhance mortality. This may be through interaction with pleiotropic functions of Mtk in the brain [46][47][48] , or through negative regulatory or direct interactions with secreted fungal molecules, which can occur with Mtk and other AMPs 64,65 . This suggests that host outcomes depend on a complex set of factors including pathogen identity and host genotype and the exact mechanism of functional differences may not simply be one allele being more potent against microbes.…”
Section: Discussionmentioning
confidence: 99%
“…In this last case, we imagine that functional Mtk might interact with the pathogen in some complex way to enhance mortality. This may be through interaction with pleiotropic functions of Mtk in the brain [46][47][48] , or through negative regulatory or direct interactions with secreted fungal molecules, which can occur with Mtk and other AMPs 64,65 . This suggests that host outcomes depend on a complex set of factors including pathogen identity and host genotype and the exact mechanism of functional differences may not simply be one allele being more potent against microbes.…”
Section: Discussionmentioning
confidence: 99%
“…When expressed with the BomS3 promoter, BomS6 was not susceptible to C. glabrata infection, but BomT2 showed no difference in susceptibility. Xu et al [3] showed that BomBc1, BomS3 and BomS4 were significantly induced upon A. fumigatus infection and that, as a whole, the Bomanin cluster enhances both resistance to, and tolerance of, infection with A. fumigatus. BomBc1, BomS3 and BomS6 increased tolerance to the fungal toxin, restrictocin, whereas Bom S6 and BomS1 increased tolerance to another toxin, verruculogen.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have attempted to characterize the role of individual Bomanin genes, the entire cluster of 10 genes, or subsets of those genes (summarized in Table 1) [1-3, 26, 46]. This began with Clemmons et al .…”
Section: Discussionmentioning
confidence: 99%